Development of Student-Centered Learning With Problem-Based Learning Through Blended Learning In 3.B Block (Normal Delivery Care) - Yulizawati Yulizawati; Henni Fitria (Universitas Andalas, 2021)
3.B Block is the second block that give students the opportunity to understand the concepts, changes and mechanisms of normal delivery, basic needs of mothers in labor, implementation of assessments of mothers in labor and neonates, determining planning, management and evaluation of labor. This study applies a blended learning and tutorial in the PBL method to improve students’ critical thinking skills. This Classroom Action Research was held at the Undergraduate Program of Midwifery, Faculty of Medicine, Andalas University. The subject of this study was the third semester student in the 2021/2022 academic year . This study compares the development of student scores from the first meeting to the fourth meeting of the tutorial. Data collection tools using assessment sheets and written tests. The results showed that the blended learning model could improve students' creative thinking skills. The increase in the average value of students' creative thinking abilities from 79,24 at the fisrt meeting to 84,69 at the fourth meeting. This study also showed the increased value of the pre-test and post-test scores of students. Where the results showed that the majority of students had a score range in 75-79 (30.30%).